Pairwise semiregular properties on generalized pairwise regular-Lindelof spaces. - Salleh, Zabidin; Kilicman, Adem (University of Istanbul Faculty of Science the Journal of Mathematics, Physics and Astronomy., 2008)
Let (X; T1; T2) be a bitopological space and (X; T8(1,2), T8(2,1))its pairwise semiregularization. Then a bitopological property P is called pair-wise semiregular provided ³ that (X; T1; T2) has the property P if and only if (X; T8(1,2), T8(2,1))has the same property. In this paper we study pairwise semiregular properties of a bitopological space. We prove that pairwise almost regular-Lindelofness and pairwise weakly regular-Lindelofness are pairwise semiregular properties.